Effect of Aerobic Exercise on The Psychological Stress State of Hypertensive Patients - Hao Li (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Hypertension may also be referred to as essential hypertension. The circulatory movement is in its early stages. Hypertension is a self-contained systemic ailment characterised by elevated arterial blood pressure, leading to detrimental effects on various organs such as the heart, brain, kidneys, and other bodily systems. The term "high" refers to a state or condition that is elevated or above average. Hypertension is a prevalent and highly morbid condition within the cardiovascular system. The prevalence of hypertension in our nation is experiencing an upward trend, with a concomitant rise in the proportion of hypertensive adults observed annually. Currently, the predominant approach to managing hypertension in our nation revolves around pharmacological interventions; however, it is worth noting that these drug treatments are associated with certain adverse effects. In the long term, there is a significant fluctuation in blood pressure following discontinuation. There is an urgent need for an improvement to be made regarding this particular phenomenon. The objective of this study is to examine the impact of aerobic exercise on stress levels, quality of life, and lipid and glucose metabolism among hypertensive adults. A total of 92 individuals diagnosed with hypertension were assigned to two groups: a control group consisting of 46 participants, and a study group also consisting of 46 participants. The allocation of individuals to each group was determined based on digital criteria. Both cohorts were administered a regimen of pharmaceutical compounds, with the experimental group additionally engaging in aerobic exercise as an adjunctive intervention. The researcher employed the Self-Assessment Scale (SAS) to assess levels of anxiety, and the Health Questionnaire (MOSSF36) to evaluate the quality of life in both experimental groups prior to and following a 10-week intervention period. In the present study, we compared the levels of total fat (TC), triacylglycerol (TG), high-density lipoprotein (HDL-C), low-density lipoprotein (LDL-C), fasting blood glucose (FPG), and insulin (FINS) in addition to insulin sensitivity index (ISI), systolic blood pressure (SBP), and diastolic blood pressure (DBP) between the two groups. Following the intervention, the study group exhibited a statistically significant decrease in SAS scores compared to both the pretreatment and control groups (P<0.05). Additionally, both the pretreatment and control groups demonstrated elevated levels of cardiac (RE) and mental health (MH) roles. The study group exhibited higher scores in physical health (PH), general health (GH), vitality (VT), role emotional (RE), and mental health (MH) compared to the control group after treatment (p < 0.05). However, there was no significant difference observed between the two groups in terms of physical pain (BP) and social functioning (SF) (p > 0.05). There were no statistically significant differences observed between the before and after treatment groups (P>0.05) in terms of LDL-C, FINS, FPG, SBP, and MP. The results of the study indicate that the observed values of HDL-C and ISI in the study group were significantly higher than those in the control group after treatment (P<0.05). Additionally, it was found that the values of HDL-C and ISI in the study group were also higher after treatment compared to their own values before treatment (P<0.05). Hypertensive diseases can be attributed to elevated hormone levels, increased blood lipid concentrations, and reduced nitric oxide levels within the body. The phenomenon is attributed to underlying factors of a lesser magnitude. Aerobic exercise interventions of extended duration have been shown to have a positive impact on both systolic and diastolic blood pressure levels in individuals diagnosed with hypertension. The reduction in blood lipids and plasma endothelin levels leads to improved blood glucose regulation and enhanced nitric oxide-mediated vasodilation, thereby contributing to the maintenance of stable blood pressure levels within the body. Aerobic exercise has been found to have a beneficial impact on stress levels, quality of life, and blood lipid profiles. The voluntary enhancement of blood glucose and blood pressure has been observed in elderly individuals with hypertension.